Significance of enriched culture on the assessment of the acute inhibitory impact of sulfamethoxazole on nitrifying biomass - Katipoglu‐Yazan, Tugce; Ubay‐Cokgor, Emine; Orhon, Derin (Wiley, 2022)
AbstractBACKGROUNDAutotrophic microorganisms are quite vulnerable to environmental conditions and to inhibitory actions that would upset nitrification mechanisms. A reliable numerical assessment of the adverse impact is needed for proper remedial action. This study focused on the kinetic response of the nitrifying fraction within the activated sludge biomass under acute exposure to sulfamethoxazole (SMX), utilizing and emphasizing the role of enriched culture. A mixed culture sustained with an enrichment technique was used to generate oxygen uptake rate profiles, where ammonia was the sole substrate with different SMX concentrations.RESULTSModel calibration studies yielded specific growth rates of 1.40/day for the ammonia oxidizing fraction and 0.65/day for the nitrite oxidizing fraction acting as the rate limiting step for the overall nitrification process. SMX did not appreciably affect the specific growth rates, but it induced a significant increase in half saturation coefficients. Moreover, increased endogenous decay rates were estimated.CONCLUSIONModel calibration values indicated that SMX induced competitive inhibition on microbial growth and enhanced endogenous respiration due to an increasing demand for the maintenance energy to activate antibiotic resistance. This underlines the merit of further studies on conditions to sustain resistant microorganisms capable of tolerating and even degrading antibiotics in biological systems. © 2022 Society of Chemical Industry (SCI).